The Merits of Urine Color Observation as a Rapid Diagnostic Technique to Estimate Schistosoma Haematobium Infection in Two Endemic Areas of Benue State, Nigeria - Houmsou, Robert; Amuta, Elizabeth; Omudu, Edward (IntechOpen, 2012)
None